Unexpected Effects of Propiconazole, Tebuconazole, and Their Mixture on the Receptors CAR and PXR in Human Liver Cells. (6th February 2018) - Knebel, Constanze; Neeb, Jannika; Zahn, Elisabeth; Schmidt, Flavia; Carazo, Alejandro; Holas, Ondej; Pavek, Petr; Püschel, Gerhard P; Zanger, Ulrich M; Süssmuth, Roderich; Lampen, Alfonso; Marx-Stoelting, Philip; et al.
Abstract: Analyzing mixture toxicity requires an in-depth understanding of the mechanisms of action of its individual components. Substances with the same target organ, same toxic effect and same mode of action (MoA) are believed to cause additive effects, whereas substances with different MoAs are assumed to act independently. Here, we tested 2 triazole fungicides, propiconazole, and tebuconazole (Te), for individual and combined effects on liver toxicity-related endpoints. Both triazoles are proposed to belong to the same cumulative assessment group and are therefore thought to display similar and additive behavior. Our data show that Te is an antagonist of the constitutive androstane receptor (CAR) in rats and humans, while propiconazole is an agonist of this receptor. Both substances activate the pregnane X-receptor (PXR) and further induce mRNA expression of CYP3A4. CYP3A4 enzyme activity, however, is inhibited by propiconazole. For common targets of PXR and CAR, the activation of PXR by Te overrides CAR inhibition. In summary, propiconazole and Te affect different hepatotoxicity-relevant cellular targets and, depending on the individual endpoint analyzed, act via similar or dissimilar mechanisms. The use of molecular data based on research in human cell systems extends the picture to refine cumulative assessment group grouping and substantially contributes to the understanding of mixture effects of chemicals in biological systems.